advertisement

advertisement

Information about Lesson 15: Inverse Functions And Logarithms

Inverse functions in general, and the inverses of very important exponential functions

advertisement

Outline Inverse Functions Derivatives of Inverse Functions Logarithmic Functions . . . . . .

What is an inverse function? Deﬁnition Let f be a function with domain D and range E. The inverse of f is the function f−1 deﬁned by: f−1 (b) = a, where a is chosen so that f(a) = b. . . . . . .

What is an inverse function? Deﬁnition Let f be a function with domain D and range E. The inverse of f is the function f−1 deﬁned by: f−1 (b) = a, where a is chosen so that f(a) = b. So f−1 (f(x)) = x, f(f−1 (x)) = x . . . . . .

What functions are invertible? In order for f−1 to be a function, there must be only one a in D corresponding to each b in E. Such a function is called one-to-one The graph of such a function passes the horizontal line test: any horizontal line intersects the graph in exactly one point if at all. If f is continuous, then f−1 is continuous. . . . . . .

Graphing an inverse function The graph of f−1 interchanges the x and y f . coordinate of every point on the graph of f . . . . . . .

Graphing an inverse function The graph of f−1 interchanges the x and y f . coordinate of every point on the graph of f .−1 f The result is that to get the graph of f−1 , we . need only reﬂect the graph of f in the diagonal line y = x. . . . . . .

How to ﬁnd the inverse function 1. Write y = f(x) 2. Solve for x in terms of y 3. To express f−1 as a function of x, interchange x and y . . . . . .

How to ﬁnd the inverse function 1. Write y = f(x) 2. Solve for x in terms of y 3. To express f−1 as a function of x, interchange x and y Example Find the inverse function of f(x) = x3 + 1. . . . . . .

How to ﬁnd the inverse function 1. Write y = f(x) 2. Solve for x in terms of y 3. To express f−1 as a function of x, interchange x and y Example Find the inverse function of f(x) = x3 + 1. Answer √ y = x3 + 1 =⇒ x = y − 1, so 3 √ f−1 (x) = 3 x−1 . . . . . .

Outline Inverse Functions Derivatives of Inverse Functions Logarithmic Functions . . . . . .

derivative of square root √ dy Recall that if y = x, we can ﬁnd by implicit differentiation: dx √ x =⇒ y2 = x y= dy =⇒ 2y =1 dx dy 1 1 =√ =⇒ = dx 2y 2x d2 y , and y is the inverse of the squaring function. Notice 2y = dy . . . . . .

Theorem (The Inverse Function Theorem) Let f be differentiable at a, and f′ (a) ̸= 0. Then f−1 is deﬁned in an open interval containing b = f(a), and 1 (f−1 )′ (b) = ′ −1 f (f (b)) . . . . . .

Theorem (The Inverse Function Theorem) Let f be differentiable at a, and f′ (a) ̸= 0. Then f−1 is deﬁned in an open interval containing b = f(a), and 1 (f−1 )′ (b) = ′ −1 f (f (b)) “Proof”. If y = f−1 (x), then f(y) = x, So by implicit differentiation dy dy 1 1 f′ (y) = 1 =⇒ =′ = ′ −1 dx dx f (y) f (f (x)) . . . . . .

Outline Inverse Functions Derivatives of Inverse Functions Logarithmic Functions . . . . . .

Logarithms Deﬁnition The base a logarithm loga x is the inverse of the function ax y = loga x ⇐⇒ x = ay The natural logarithm ln x is the inverse of ex . So y = ln x ⇐⇒ x = ey . . . . . . .

Logarithms Deﬁnition The base a logarithm loga x is the inverse of the function ax y = loga x ⇐⇒ x = ay The natural logarithm ln x is the inverse of ex . So y = ln x ⇐⇒ x = ey . Facts (i) loga (x · x′ ) = loga x + loga x′ . . . . . .

Logarithms Deﬁnition The base a logarithm loga x is the inverse of the function ax y = loga x ⇐⇒ x = ay The natural logarithm ln x is the inverse of ex . So y = ln x ⇐⇒ x = ey . Facts (i) loga (x · x′ ) = loga x + loga x′ (x) (ii) loga ′ = loga x − loga x′ x . . . . . .

Logarithms Deﬁnition The base a logarithm loga x is the inverse of the function ax y = loga x ⇐⇒ x = ay The natural logarithm ln x is the inverse of ex . So y = ln x ⇐⇒ x = ey . Facts (i) loga (x · x′ ) = loga x + loga x′ (x) (ii) loga ′ = loga x − loga x′ x (iii) loga (xr ) = r loga x . . . . . .

Logarithms convert products to sums Suppose y = loga x and y′ = loga x′ ′ Then x = ay and x′ = ay ′ ′ So xx′ = ay ay = ay+y Therefore loga (xx′ ) = y + y′ = loga x + loga x′ . . . . . .

Example Write as a single logarithm: 2 ln 4 − ln 3. . . . . . .

Example Write as a single logarithm: 2 ln 4 − ln 3. Solution 42 2 ln 4 − ln 3 = ln 42 − ln 3 = ln 3 ln 42 not ! ln 3 . . . . . .

Example Write as a single logarithm: 2 ln 4 − ln 3. Solution 42 2 ln 4 − ln 3 = ln 42 − ln 3 = ln 3 ln 42 not ! ln 3 Example 3 Write as a single logarithm: ln + 4 ln 2 4 . . . . . .

Example Write as a single logarithm: 2 ln 4 − ln 3. Solution 42 2 ln 4 − ln 3 = ln 42 − ln 3 = ln 3 ln 42 not ! ln 3 Example 3 Write as a single logarithm: ln + 4 ln 2 4 Answer ln 12 . . . . . .

“. . lawn” . Image credit: Selva . . . . . . .

Graphs of logarithmic functions y . . = 2x y y . = log2 x . . 0, 1) ( ..1, 0) . x . ( . . . . . .

Graphs of logarithmic functions y . . = 3x= 2x y. y y . = log2 x y . = log3 x . . 0, 1) ( ..1, 0) . x . ( . . . . . .

Graphs of logarithmic functions y . . = .10x 3x= 2x y y=. y y . = log2 x y . = log3 x . . 0, 1) ( y . = log10 x ..1, 0) . x . ( . . . . . .

Graphs of logarithmic functions y . . = .10=3xx 2x yxy y y. = .e = y . = log2 x y . = ln x y . = log3 x . . 0, 1) ( y . = log10 x ..1, 0) . x . ( . . . . . .

Change of base formula for exponentials Fact If a > 0 and a ̸= 1, then ln x loga x = ln a . . . . . .

Change of base formula for exponentials Fact If a > 0 and a ̸= 1, then ln x loga x = ln a Proof. If y = loga x, then x = ay So ln x = ln(ay ) = y ln a Therefore ln x y = loga x = ln a . . . . . .

Section 3.2Inverse Functions and LogarithmsV63.0121, Calculus IMarch 4/9/10, 2009Image credit: Roger SmithOutlineInverse FunctionsDerivatives of Inverse ...

Read more

When you graph both the logarithmic function and its inverse, ... [Back to Rules of Logarithms] [Back to Exponential Functions] [Trigonometry] ...

Read more

This lesson will review the material in Section 1.5 on Logarithms and Inverse functions. Please refer to your book for additional help.

Read more

... Exponential and Logarithmic Functions 5.1 Inverse Functions 5.2 Exponential Functions 5.3 Logarithms and Their Properties 5.4 Logarithmic ...

Read more

An exponential function is the inverse of a logarithm ... Exponential functions and logarithmic functions with base b are ... First Lesson on Logarithms.

Read more

Inverse Functions and Logarithms DEFINITION: ... 14. The function f(x) = (x+1)2 is not invertible. 15. Let f(x) = x2,x ≥ 0, then f−1(x) = ...

Read more

Learning Targets. I can identify one-to-one function; I can determine the algebraic and graphical representation of a function and its inverse; I can use ...

Read more

Example of finding the equation of the inverse of a logarithmic function. Skip ... ² Logarithms ... by mathbff 130,546 views. 19:15 ...

Read more

## Add a comment